Causality between exchange rates and stock prices: evidence from Malaysia and Thailand - Ai-Yee Ooi; Syed Azizi Wafa Syed Khalid Wafa; Nelson Lajuni; Mohd Fahmi Ghazali (CCSE, 2009)
This study analyses the causal relationship between exchange rates and stock prices for Thailand and Malaysia. By using daily data from 1993 to 2003, this study attempts to examine the relationship between exchange rates and stock prices in Thailand and Malaysia during pre and post financial crisis. The paper also investigates the long-run relationship between the above-mentioned variables using Johansen-Juselius (1990) cointegration test and short-run dynamic causal relationship by using Toda-Yamamoto (1995) procedure. Likewise, variance decompositions (VDCs) analysis is employed to improve the predictable portion of exchange rate (stock price) changes on the forecast error variance in stock prices (exchange rates). Data from Thailand demonstrates the results predicted by the portfolio balance approach: stock prices lead exchange rates in both pre-crisis and post-crisis periods; however, Malaysian findings support portfolio approach in post-crisis.